EFFECT OF HYBRID ORGANIZATION, TRANSFORMATIONAL LEADERSHIP AND CAREER DEVELOPMENT ON INCREASING DOCTORS’ PERFORMANCE - Nur Pudyastuti Pratiwi; Heru Setiawan; Mohammad Sidik Priadana (Journal of Innovation Research and Knowledge, 2022)
The hospital’s performance is influenced by the performance of health human resources. Hospital organizational structure, leadership, and career development can affect motivational change. This study aims to determine and analyze Hybrid Organizational Structure Implementation, Transformational Leadership, and Career Development on Work Motivation Improvement and its Implications on Doctors' Performance in Indonesian Army Hospital in West Java. This research was a quantitative research that used a descriptive and verificative approach with a cross-sectional survey method and explanatory. This study used a sampling technique "proportionate cluster random sampling" with 105 samples of doctors which was determined using the Slovin formula. The analytical method in this study used Structural Equation Modeling (SEM) with LISREL 8.7. The results show that Hybrid Organizational Structure Implementation, Transformational Leadership, and Career Development affected Doctor's Work Motivation Improvement partially or simultaneously. The biggest influence on Doctor's Work Motivation Improvement comes from Transformational Leadership. Furthermore, Doctor's Work Motivation Improvement has a strong effect on Doctor's Performance according to this study